2022
DOI: 10.1177/02654075211059538
|View full text |Cite
|
Sign up to set email alerts
|

Romantic conflict narratives and associations with psychological relationship aggression in emerging adult couples

Abstract: This cross-sectional study aimed to understand how emerging adult couples interpreted relationship conflicts, and whether such meaning making was associated with psychological relationship aggression and moderated by gender. We specified the I Cubed model of relationship aggression to examine how in the context of recounting relationship conflicts, the impellance factors of anger and break-up anxiety might increase and the inhibition factor of perspective taking might decrease the likelihood of relationship ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…Taken together, the prior research suggests that greater perspective taking provides a more balanced, less self-focused understanding of relationship interactions and partner behavior that should reduce the degree to which actors behave negatively. However, the most direct evidence that perspective taking reduces negative behavioral responses relies on general reports of perspective taking and behavioral tendencies (e.g., Arriaga & Rusbult, 1998; Corcoran & Mallinckrodt, 2000; Loudin et al, 2003; Rizkalla et al, 2008), coding descriptions of past partner transgressions (e.g., Feiring et al, 2020, 2022), or reported responses to hypothetical scenarios (e.g., Arriaga & Rusbult, 1998). These methods offer relatively weak tests of whether perspective taking attenuates actors’ negative behaviors as couples respond to each other within relationship interactions.…”
Section: Perspective Taking and Negative Behavior In Relationship Int...mentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, the prior research suggests that greater perspective taking provides a more balanced, less self-focused understanding of relationship interactions and partner behavior that should reduce the degree to which actors behave negatively. However, the most direct evidence that perspective taking reduces negative behavioral responses relies on general reports of perspective taking and behavioral tendencies (e.g., Arriaga & Rusbult, 1998; Corcoran & Mallinckrodt, 2000; Loudin et al, 2003; Rizkalla et al, 2008), coding descriptions of past partner transgressions (e.g., Feiring et al, 2020, 2022), or reported responses to hypothetical scenarios (e.g., Arriaga & Rusbult, 1998). These methods offer relatively weak tests of whether perspective taking attenuates actors’ negative behaviors as couples respond to each other within relationship interactions.…”
Section: Perspective Taking and Negative Behavior In Relationship Int...mentioning
confidence: 99%
“…Other self-report studies suggest that perspective taking should be particularly valuable in reducing negative behavior when actors face negative behavior by their partner. Feiring and colleagues (Feiring et al, 2020, 2022) found that, although actors tend to recount their partner’s negative behavior as being intentionally hurtful, narratives that involve greater perspective taking also include less aggressive responses by actors and less conflict escalation. Similarly, Arriaga and Rusbult (1998) illustrated that instructed perspective taking was associated with less partner blaming attributions and lower self-reported tendencies to retaliate against partner’s hypothetical negative behavior.…”
Section: Perspective Taking and Negative Behavior In Relationship Int...mentioning
confidence: 99%
“…Relationship uncertainty is associated with more negative emotion and appraisals of irritation as more severe and relationally threatening (e.g., Solomon et al, 2016). In our pre‐pandemic narrative work on emerging adult romantic relationships, we have consistently observed that for some partners, specific conflict events may be viewed as a source of worry about whether the relationship should or will continue, an interpretation we call break‐up anxiety (Feiring et al, 2018; Feiring, Liang, et al, 2022; Feiring, McMahon, & Gall, 2022). Both the BUA and uncertainty constructs share the idea that partners are unsure about the nature and future of the relationship.…”
Section: Relationship Uncertainty and Interferencementioning
confidence: 99%
“…In interpersonal contexts, anger is viewed as a likely response to a sense of being injured, unjustly treated, or thwarted (Birkley & Eckhardt, 2015). In conflict narratives, as well as daily diaries and observations of romantic conflict, anger is associated with the increased likelihood of reacting aggressively (Crane & Testa, 2014; Feiring, Liang, et al, 2022). Sadness, in contrast to anger, is viewed as indicating a partner's tendency to interpret conflict events from a more vulnerable than defensive stance.…”
Section: Relationship Uncertainty and Interferencementioning
confidence: 99%
“…In a society, understanding the cognitive perspective of others can encourage altruistic motivation (Batson et al, 1997;Trötschel et al, 2011), and increase the probability of reaching an agreement during negotiations (Galinsky et al, 2008). CPT can also decrease stereotypical expressions (Galinsky & Moskowitz, 2000), and aggressive behavior (Feiring et al, 2022;Richardson et al, 1994).…”
Section: Introductionmentioning
confidence: 99%